3D hierarchical porous N-doped carbon nanosheets/MgFe2O4 composite as anode material with excellent cycling stability and rate performance. (December 2020) - Liu, Wenfeng; Gao, Rongzhen; Yin, Yanhong; Cui, Yuantao; Yue, Hongyun; Dong, Hongyu; Yang, Shuting
Abstract: 3D hierarchical porous N-doped carbon nanosheets/MgFe2 O4 (MFO/NPC) was designed and synthesized successfully as the anode materials for lithium ion batteries by freeze-drying technology with dual salt templates and subsequent in-situ solvent thermal method. Its specific capacity rises steadily to 1337.7 mAh g −1 at the 260th cycle with the initial coulombic efficiency of 78.3% (0.5 A g −1 ). And the capacity remains at 534.1 mAh g −1 even after 1500 cycles at the current density of 5 A g −1 . The excellent electrochemical performances can be attributed to the 3D conductive carbon skeleton and the chemical interaction between MFO and the doped N element. Graphical Abstract: 3D hierarchical porous N-doped carbon nanosheets /MgFe2 O4 (MFO/NPC) was designed and synthesized successfully as the anode materials for lithium ion batteries by freeze-drying technology with dual templates (NaCl and Na2 SiO3 ) and subsequent in-situ solvent thermal method. Due to the compositing with the 3D hierarchical porous carbon nanosheets and the chemical interaction between MFO and the doped N, the obtained material shows excellent cycling stability, rate performance and relatively high initial coulombic efficiency. A reversible specific capacity still remains at 534.1 mAhg −1 even after a long-cycle of 1500 cycles at the high current density of 5 Ag −1 . Image, graphical abstract